2021
DOI: 10.3390/compounds1010005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Spark Plasma Sintering-Processed Pure Ti and Ti-6Al-4V Alloys: A Comparative Study between Harmonic and Non-Harmonic Microstructures

Abstract: Microstructure characteristics and compressive property relationships of so-called harmonic (composed by fine and coarse grains) and conventional pure titanium (Ti) and Ti-6Al-4V alloy processed by powder metallurgy route are presented in the present work. Electron backscatter diffraction (EBSD) analysis was performed to characterize the as-processed microstructures. The harmonicity structure of selected samples is described, and relevant EBSD maps are presented. The bulk samples’ hardness is reported, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In addition, exploring alternative machine learning algorithms could be beneficial to determine whether they yield more accurate predictions or provide deeper insights into the behavior of biocomposites. It would also be worthwhile to explore the application of these techniques to other materials, such as Ni-W with a composite-like microstructure [49][50][51], dissimilar welding joints [52], or harmonic alloys [53,54]. An R 2 value of 0.94 was obtained for the decision tree model, while the random forest model achieved a value of 0.95.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, exploring alternative machine learning algorithms could be beneficial to determine whether they yield more accurate predictions or provide deeper insights into the behavior of biocomposites. It would also be worthwhile to explore the application of these techniques to other materials, such as Ni-W with a composite-like microstructure [49][50][51], dissimilar welding joints [52], or harmonic alloys [53,54]. An R 2 value of 0.94 was obtained for the decision tree model, while the random forest model achieved a value of 0.95.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the fact that the machine learning models are highly affected by this parameter is very relevant. Machine learning is a very pertinent method that should be considered to predict output values from several input variables that are not linearly dependent in other cases such as the study of mechanical properties of alloys [24][25][26][27][28][29][30], composites [31][32][33][34][35] or ceramics materials [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…14 Despite FAST furnaces becoming more common in research institutes and industry, the reporting of mechanical properties from FAST-processed materials is often limited due to the typically small samples produced. 10 Mechanical properties of FAST-processed titanium alloys have been obtained by compression testing [15][16][17] and inferred from hardness testing. 15,16,18 Tensile strengths from sub-size test specimens have also been reported; for example, ∼350 MPa with ∼30% elongation for < 45 µm GA grade 1 CP-Ti and ∼600 MPa with ∼15% elongation for < 45 µm angular grade 3 CP-Ti, 19 978-1045 MPa with 6.3-18.2% elongation for < 45 µm GA Ti-6Al-4V, 20 1240 MPa with 19.5% elongation for 75-150 µm GA Ti-6Al-4V through manipulation of FAST load and temperature to create a 'bimorphic' microstructure, 21 844/893 MPa with 12/17% elongation for 53-106 µm GA Ti-6Al-4V either as-FAST or with subsequent heat treatment, 22 and 1183 MPa with 6% elongation for Ti-5Al-5V-5Mo-3Cr created from blended elemental 10-80 µm angular and spherical powders.…”
Section: Introductionmentioning
confidence: 99%
“…10 Mechanical properties of FAST-processed titanium alloys have been obtained by compression testing [15][16][17] and inferred from hardness testing. 15,16,18 Tensile strengths from sub-size test specimens have also been reported; for example, ∼350 MPa with ∼30% elongation for < 45 µm GA grade 1 CP-Ti and ∼600 MPa with ∼15% elongation for < 45 µm angular grade 3 CP-Ti, 19 978-1045 MPa with 6.3-18.2% elongation for < 45 µm GA Ti-6Al-4V, 20 1240 MPa with 19.5% elongation for 75-150 µm GA Ti-6Al-4V through manipulation of FAST load and temperature to create a 'bimorphic' microstructure, 21 844/893 MPa with 12/17% elongation for 53-106 µm GA Ti-6Al-4V either as-FAST or with subsequent heat treatment, 22 and 1183 MPa with 6% elongation for Ti-5Al-5V-5Mo-3Cr created from blended elemental 10-80 µm angular and spherical powders. 23 Several studies have also examined the potential to enhance mechanical properties of titanium alloys by performing extensive milling of the powders prior to FAST consolidation [24][25][26][27][28] ; although it was reported that the fatigue life of both un-milled and milled powders was 74% of the materials' tensile strength.…”
Section: Introductionmentioning
confidence: 99%